2022
DOI: 10.1177/19476035221109242
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lesion Size on Pain and Function in Patients Scheduled for Cartilage Surgery of the Knee

Abstract: Objective Despite an increased interest in treatment options for cartilage lesions of the knee, the relationship between lesion characteristics and the symptoms they elicit is not well understood. We evaluated the relationship between lesion characteristics and the patient-reported outcome measures (PROMs) and compared this with symptoms reported by patients scheduled for knee ligament reconstruction and knee arthroplasty. Design Preoperative data, including Lysholm score and The Knee Injury and Osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There could have been a discrepancy in the preoperative KOOS scores between the groups. However, several studies have demonstrated PREVIOUS CARTILAGE SURGERY AFTER KNEE ARTHROPLASTY | 367 that cartilage patients have similar KOOS QoL subscores to patients awaiting knee arthroplasty [2,3], indicating that the preoperative PROM in the cartilage cohort might be comparable to those in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There could have been a discrepancy in the preoperative KOOS scores between the groups. However, several studies have demonstrated PREVIOUS CARTILAGE SURGERY AFTER KNEE ARTHROPLASTY | 367 that cartilage patients have similar KOOS QoL subscores to patients awaiting knee arthroplasty [2,3], indicating that the preoperative PROM in the cartilage cohort might be comparable to those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Focal cartilage lesions (FCLs) in the knee exhibit poor natural healing capabilities [1] and may significantly reduce quality of life (QoL) [2,3]. Even in surgically treated FCLs, normal knee function is often not achieved [4].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of OA is usually accompanied by cartilage injury and abnormal changes of subchondral bone. In the investigation of human OA, partial or full-layer defects of articular cartilage were found in patellofemoral joints during surgery and autopsy [ 30 , 31 ]. Compared with femoral trochlear cartilage, the fibrosis, longitudinal fissure and softening swelling of human patella cartilage in the early stage are more obvious and serious [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions are typically defined by defect size and severity, with common size cutoffs cited in the literature (small, <2 cm 2 ; medium, 2 cm 2 to 5 cm 2 ; and large, >5 cm 2 ) 17 . There are several intraoperative classification systems to grade severity of chondral defects, including the Outerbridge arthroscopic system and the International Cartilage Repair Society (ICRS) classification system 18,19 .…”
Section: Classification Of Articular Cartilage and Bone Defectsmentioning
confidence: 99%